2017
DOI: 10.1071/mf15326
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the trophic structure of fish communities between artificial and natural habitats in a tropical estuary

Abstract: The present study tested the hypothesis that artificial habitats (pier and bridge) harbour different fish trophic guilds compared with natural habitats (mangrove roots) and that the trophic structure of fish communities on estuarine artificial habitats resembles adjacent coral reefs. High-definition cameras were used to survey the fish community associated with the different structures over a 6-month period. Benthos was also analysed following the point intercept method on the different habitats. In the estuar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…However, one study in the Hudson River estuary observed similarly low abundances of fish in uncovered piling fields and under piers relative to open waters, potentially because pilings may disrupt the formation of schools or hide ambush predators (Grothues, Rackovan & Able 2016). Conversely, fish were more abundant and of a different trophic structure under a comparatively narrow pier and bridge along the estuary of Rio Formoso (PE, Brazil), probably because the piling structures provided unique prey, and the shade cast by these structures was less intense than in other studies (Pereira et al 2017).…”
Section: Documented Effects Of Overwater Structures On Fishmentioning
confidence: 67%
See 1 more Smart Citation
“…However, one study in the Hudson River estuary observed similarly low abundances of fish in uncovered piling fields and under piers relative to open waters, potentially because pilings may disrupt the formation of schools or hide ambush predators (Grothues, Rackovan & Able 2016). Conversely, fish were more abundant and of a different trophic structure under a comparatively narrow pier and bridge along the estuary of Rio Formoso (PE, Brazil), probably because the piling structures provided unique prey, and the shade cast by these structures was less intense than in other studies (Pereira et al 2017).…”
Section: Documented Effects Of Overwater Structures On Fishmentioning
confidence: 67%
“…Conversely, fish were more abundant and of a different trophic structure under a comparatively narrow pier and bridge along the estuary of Rio Formoso (PE, Brazil), probably because the piling structures provided unique prey, and the shade cast by these structures was less intense than in other studies (Pereira et al . ).…”
Section: Documented Effects Of Overwater Structures On Fishmentioning
confidence: 97%
“…However, the availability of food resources is one of the factors that influence the existence of fishes. Previous studies have also established that a correlation exists between the structure of the digestive apparatus and the feeding habits of fishes (Pereira et al 2016;Lopez-Rodriguez et al 2019;Manna et al 2020).…”
Section: Introductionmentioning
confidence: 92%
“…The huge value is expected because the fish are able to utilize the resources available in large quantities. However, this value is influenced by the number of the different types of food consumed by a particular group of fish with a relatively large niche area tends to have an increased number of species that are utilized as their food sources (Tresna et al 2012;Pereira et al 2016). It also implies that the fish group tends to evenly utilize all available resources in the aquatic environment as their natural diets.…”
Section: Feeding Niches Areamentioning
confidence: 99%
“…These include trophic relations of fish in South African estuaries (Whitfield, 1980;Whitfield, 2020b), Guadalquivir Estuary (Baldo & Drake, 2002), the eastern boundary of the San Francisco Estuary (Grimaldo et al, 2009) and the Chesapeake Bay (Buchheister & Latour, 2015). Some studies have assessed the feeding ecology of fishes in different types of ecosystem (Braga et al, 2012;Elena et al, 2020), such as the abyssal and hadal zones of Kermadec and Mariana Trenches (Gerringer et al, 2017), reef fish in a remote oceanic island at the Juan Fernandez Archipelago, Chile (Ramírez et al, 2013), the largest hypersaline Araruama Lagoon on the east coast of South America (Almeida-Silva et al, 2015), northeast Brazil (Pereira et al, 2016), the rocky reefs in Australia (Truong et al, 2017), the Little Colorado River, Arizona (Behn & Baxter, 2019) and the North Yellow Sea, China (Rongliang et al, 2021). In South East Asia, besides healthy fish resources facing severe reduction from various factors (FAO, 2020), studies of fish trophic ecology are, however, limited.…”
mentioning
confidence: 99%